Cardiomyocyte proliferation and heart regeneration in adult Xenopus tropicalis evidenced by a transgenic reporter line - Xiao-Lin Lin; Jin-Hua Lin; Yan Cao; Han Zhang; Si-Yi He; Hai-Yan Wu; Ze-Bing Ye; Li Zheng; Xu-Feng Qi (npj Regenerative Medicine)
Abstract Cardiomyocyte proliferation in adult Xenopus tropicalis during heart regeneration has remained largely contentious due to the absence of genetic evidence. Here, we generated a transgenic reporter line Tg(mlc2:H2C) expressing mCherry specifically in cardiomyocyte nuclei driven by the promoter of myosin light chain 2 (mlc2). Using the reporter line, we found that traditional whole-cell staining is not a rigorous way to identify cardiomyocytes in adult Xenopus tropicalis when using a cryosection with common thickness (5 μm) which leading to a high error, but this deviation could be reduced by increasing section thickness. In addition, the reporter line confirmed that apex resection injury greatly increased the proliferation of mlc2 + cardiomyocytes at 3-30 days post-resection (dpr), thereby regenerating the lost cardiac muscle by 30 dpr in adult Xenopus tropicalis. Our findings from the reporter line have rigorously defined cardiomyocyte proliferation in adult heart upon injury, thereby contributing heart regeneration in adult Xenopus tropicalis.